PREVALENCE OF HYPERTENSION AND WAIST/HIP RATIO (WHR) AND BODY MASS INDEX (BMI) IN STUDENTS (Fiep Bulletin - online, 2013)
The objective of this study relates to the WHR, BMI, blood pressure and health of students. The research was undertaken with 117 students, both genders, aged between 14 and 17 years. The waist hip ratio (WHR) was measured using a tape measure; the body mass index (BMI) was based on the body mass in Kg and height in cm, and blood pressure measured at rest. Regression analysis was used to verify the correlation between samples, considering r between 1 and -1. It was observed that 50% of the 14-year old male students exhibited some level of malnutrition; with 25% overweight and 25% grade I obese. Among 15-year old students, 42% were underweight; 33% normal weight; 17% grade II obese and 8% overweight. For 16-year olds, results were 41% normal weight; 17% underweight; 17% overweight; 17% grade I obese, and 8% malnourished. For 17-year old males results were 55% normal weight; 15% underweight; 11% overweight; 11% grade I obese; 6% malnourished, and 6% grade II obese. Among female students, 50% were normal weight and 50% underweight for 14-year olds. For 15-year olds 73% had normal weight; 9% malnourished; 9% underweight and 9% grade I obese. Among 16-year old girls it was observed that 62% had normal weight; 25% were malnourished, and 13% underweight. For 17-year olds the results were 63% normal weight; 25% underweight and 12% malnourished. In relation to WHR, all the males evaluated had results less than 0.95, indicating that they don't present risk of developing diseases. Among the evaluated females, 100% had WHR values greater than 0.80 indicating risk for disease development. It can be observed that the blood pressure levels were within the normal range for both genders and all age groups examined, with slightly higher values among 14-year old girls.
Keywords: blood pressure; body mass index; WRH